Protection from diclofenac-induced liver injury by Yulangsan polysaccharide in a mouse model. (4th December 2016) - Huang, Jianchun; Nguyen, Vanphuc; Tang, Xiaojun; Wei, Jinbin; Lin, Xing; Lai, Zefeng; Doan, Vanminh; Xie, Qiuqiao; Huang, Renbin
Abstract: Ethnopharmacological relevance: Millettia pulchra Kurz var-laxior (Dunn) Z. Wei, a wild-growing plant of the family Fabaceae is known to possess multifarious medicinal properties. Yulangsan polysaccharide (YLSPS) is a chief ingredient of its root, which has been used in Chinese traditional medicine with a long history for remedy of acute or chronic hepatitis and jaundice. Aim of the study: To investigate the ability of the YLSPS to protect against diclofenac-induced hepatotoxicity in mice. Materials and methods: Mice were orally treated with YLSPS daily 1 h after the injection of diclofenac for 2 weeks. Dimethyl diphenyl bicarboxylate was used as a reference drug. Results: YLSPS effectively reduced the elevated levels of serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase and enhanced the reduction of superoxide dismutase, catalase, and glutathione peroxidase activities in the liver. Moreover, the content of malondialdehyde was reduced by treatment with YLSPS, and histological findings also confirmed the anti-hepatotoxic activity. In addition, YLSPS significantly inhibited proinflammatory mediators, such as tumor necrosis factor-alpha and interleukin 1 beta. YLSPS also enhanced mitochondrial antioxidants and inhibited cell death by preventing the down-regulation of Bcl-2 and the up-regulation and release of Bax along with caspase 9 and 3 activity; thus, these findings confirm the involvement of mitochondria in diclofenac-induced apoptosis. Conclusion: The results indicate that protective effects of YLSPS against diclofenac-induced acute hepatic injury may rely on its effect on reducing oxidative stress, suppressing inflammatory responses, and improving drug-metabolizing enzyme activity in the liver. Graphical abstract: